The Effects of the Working Environment of Firefighters on the Quality of Life - Choi, Hee-Chul (Fire Science and Engineering, 2020)
This study aimed to contribute to the preparation of an action plan for the improvement of the quality of life of firefighters at the individual level by examining how the working environment as perceived by firefighters affects their quality of life. To this end, this study conducted a survey that used purposive sampling targeting 201 fire-fighting officers in Incheon. The survey results showed that of the sub-variables of the working environment of firefighters, monetary rewards, challenges, and promotion had a significant influence on the quality of life. Based on the results, this study suggested various action plans that can support the working environment and improve the quality of life of firefighters.